2022
DOI: 10.3390/ma15051782
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Engineering Characteristics and Microscopic Mechanism of Red Mud–Bauxite Tailings Mud Foam Light Soil

Abstract: In order to effectively utilize aluminum industrial waste—red mud and bauxite tailings mud—and reduce the adverse impact of waste on the environment and occupation of land resources, a red mud–bauxite tailings mud foam lightweight soil was developed based on the existing research results. Experiments were conducted to investigate the mechanical properties and microscopic characteristics of the developed materials with different proportions of red mud and bauxite tailings mud. Results show that with the increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…The physical and mechanical behaviour, fracture, damage, and evolution processes of geomaterials under various environmental and mechanical conditions, such as thermal, mechanical, chemical, and electrical environments [6][7][8][9][10][11][12][13][14][15][16][17]20,21].…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
See 2 more Smart Citations
“…The physical and mechanical behaviour, fracture, damage, and evolution processes of geomaterials under various environmental and mechanical conditions, such as thermal, mechanical, chemical, and electrical environments [6][7][8][9][10][11][12][13][14][15][16][17]20,21].…”
Section: Short Description Of the Articles Presented In This Special ...mentioning
confidence: 99%
“…This Special Issue covers numerous aspects of functional mineral research. These topics focus on various themes, including the analysis of mineralogical composition and its effects on the physico-mechanical properties of geomaterials, the investigation of the impact of triaxial stress on the damage creep behaviour of geomaterials, and the evaluation of the thermophysical and mechanical characteristics of rocks under high-temperature circumstances [6][7][8][9][10][11][12][13][14]. The research conducted on these topics also involves various experimental and numerical techniques, such as digital image processing, Discrete Element Method (DEM), and analytical solution and simulation [13,[15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Eggshells have such great potential in the application of cement-based materials that their use has attracted the attention of many researchers [ 23 , 24 , 25 , 26 , 27 , 28 , 29 ]. Jhatial et al [ 30 ] reported that the eggshell can be used as auxiliary cementitious material after being ground into powder.…”
Section: Introductionmentioning
confidence: 99%
“…These particles can easily affect the stability and impermeability of tailings in a dam, which may lead to the formation of hazardous dams [ 1 ]. With the progress of solid waste utilization technology, coarse-grained tailings can be considered as a mineral in different applications [ 2 ], such as building materials and roadbed construction [ 3 ]. This development is a key measure to build tailless mines, reuse the resources of coarse-grained tailings after grading, fill underground empty areas with classified fine tailings, and achieve 100% comprehensive utilization of tailing resources [ 4 , 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%